Do different vaginal tapes need different suburethral incisions? The one‐half rule. Issue 8 (30th August 2014) - Viereck, Volker; Kuszka, Andrzej; Rautenberg, Oliver; Wlaźlak, Edyta; Surkont, Grzegorz; Hilgers, Reinhard; Eberhard, Jakob; Kociszewski, Jacek
<x xml:space="preserve">Abstract</x> Aim Despite a wide array of vaginal tapes to treat stress urinary incontinence (SUI), evidence suggesting that both patient characteristics and tape positioning influence outcomes, and differing tape insertion pathways (retropubic vs. transobturator), it remains unclear if the same incision location is effective for all tapes. The aim of the study was to compare outcomes using two different surgical incision locations when inserting a transobturator vaginal tape (TOT) to treat SUI. Methods We compared patient characteristics, tape positioning, and surgical outcomes in 123 women undergoing a TOT procedure who were randomly assigned to have the surgical incision begin at 1/3 of the sonographically‐measured urethral length (similar to the traditional retropubic approach) or 1/2 of the urethral length. Results It was feasible to place the tape according to intention in 99.2% of the study cohort. The overall cure rate was higher when the incision site began at 1/2 the urethral length (83.6%) than 1/3 (62.9%) (P = 0.01). In the subgroup analyses, only patients with normal urethral mobility had significantly different cure rates (85.7% vs. 55.2%, P = 0.02). No significant differences in cure rates were observed between the other mobility categories of the study groups—hypermobility was consistently associated with high cure rates and hypomobility with low cure rates. Conclusions When surgically treating SUI with a TOT, incision at the mid‐urethra using the 1/2 rule is recommended as it leads to better outcomes for most patients, particularly those with normal urethral mobility. Neurourol. Urodynam. 34:741–746, 2015. © 2014 Wiley Periodicals, Inc.